DNA i-motif formation at neutral pH is driven by kinetic partitioning - Školáková, Petra; Gajarský, Martin; Palacký, Jan; Šubert, Denis; Renčiuk, Daniel; Trantírek, Lukáš; Mergny, Jean-Louis; Vorlíčková, Michaela (Nucleic acids research, 2023)
Cytosine-rich DNA regions can form four-stranded structures based on hemi-protonated C.C+ pairs, called i-motifs (iMs). Using CD, UV absorption, NMR spectroscopy, and DSC calorimetry, we show that model (CnT3)3Cn (Cn) sequences adopt iM under neutral or slightly alkaline conditions for n > 3. However, the iMs are formed with long-lasting kinetics under these conditions and melt with significant hysteresis. Sequences with n > 6 melt in two or more separate steps, indicating the presence of different iM species, the proportion of which is dependent on temperature and incubation time. At ambient temperature, kinetically favored iMs of low stability are formed, most likely consisting of short C.C+ blocks. These species act as kinetic traps and prevent the assembly of thermodynamically favored, fully C.C+ paired iMs. A higher temperature is necessary to unfold the kinetic forms and enable their substitution by a slowly developing thermodynamic structure. This complicated kinetic partitioning process considerably slows down iM folding, making it much slower than the timeframes of biological reactions and, therefore, unlikely to have any biological relevance. Our data suggest kinetically driven iM species as more likely to be biologically relevant than thermodynamically most stable iM forms.
Keywords: DNA; Nucleotide Motifs; Nucleic Acid Conformation; Kinetics; koncentrace vodíkových iontů; nukleotidové motivy; kinetika; konformace nukleové kyseliny; Hydrogen-Ion Concentration